The Effect Of Financial Literacy And E-Wallet Use On Students' Consumer Behavior - Tanjung, Muhammad Affandy; Hardana, Ali; Harahap, Takdir Novriansyah; Nasutin, Abri (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This study aims to analyze the effect of financial literacy and e-wallet usage on the consumptive behavior of students at the Faculty of Islamic Economics and Business, Syekh Ali Hasan Ahmad Addary State Islamic University Padangsidimpuan. The research employed a quantitative approach with a causal associative design. The sample consisted of 65 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 22.The results indicate that financial literacy has a negative effect on consumptive behavior, with a regression coefficient of -0.203, meaning that higher levels of financial literacy are associated with lower levels of consumptive behavior among students. E-wallet usage also shows a negative effect on consumptive behavior, with a regression coefficient of -0.154. Simultaneously, financial literacy and e-wallet usage have a significant effect on consumptive behavior, as evidenced by an F-test significance value of 0.001 (< 0.05). The coefficient of determination (R Square) of 0.823 indicates that 82.3% of the variation in consumptive behavior can be explained by the two independent variables.In conclusion, improving financial literacy and promoting wise use of e-wallets can be effective strategies to reduce consumptive behavior among students in the digital era.